From Radicalism to Conformism: Post-Soviet Ideological Trajectory of Russian Communist Party in 1993–2022 - Georgy A. Mayorov (СибСкрипт)
The Communist Party remains one of the leading political powers in the Russian Federation. However, it went through a major ideological evolution in 1993–2022. The article introduces a comprehensive historical analysis of the 30 years of post-Soviet Communist ideology in Russia reflected in the views of Communist leaders on the main doctrinal issues in the changing historical context. The author combined historical-genetic and comparative methods to trace the stages of these ideological changes as a historical sequence, as well as to link them with the political transformations. The comparative method made it possible to see the differences between the ideological and political contexts in the 1990s and 2020s. The Communist Party of the Russian Federation appeared during a deep crisis of Communist ideology. As a result, the party became as a synthetic entity that combined traditional communist values with elements of national patriotic discourse. In the 1990s, it emerged as the leading opposition to Yeltsin’s regime. At the turn of the 1990s–2000s, its ideology shifted from classical Marxism-Leninism to a synthesis of leftist and patriotic ideas, i.e., from internationalism to statehood, from atheism to recognition of traditional religions, etc. In the 2000s, the Communist Party integrated the regime of managed democracy as a systemic opposition. The 2010s–2020s saw a further erosion of the communist identity: as the national-patriotic and conservative tendencies kept increasing, the party abandoned any attempts to change the socio-economic system. Currently, the Communist Party is going through a contradiction between radical rhetoric and conformist practice. Historically, the Communist movement always found it very difficult to adapt to market economy and political pluralism.